Functional testing of the lower extremity muscles - P.O. Sirenko; I.P. Storozhenko; J. Žīdens; A. Zuša; O.P. Yuzyk; D. Lietuviete; T.V. Kolesnyk (Medičnì Perspektivi)
The purpose of the study was to increase the efficiency of diagnostics of the strength indicators of the lower extremity muscles by determining the optimal conditions for the mutual location of segments of kinematic links for the best implementation of contractile capabilities during functional testing. The main focus of the work was to determine the positions for the maximum overlaying of myofilaments in the sarcomeres of the investigated contractile areas of the movable segments of the lower extremities during power loads. 20 experienced football players, whose average age was 26.8±6.2 years, took part in the study. In order to fulfill the set goal, interference electromyography was performed on all athletes. The function of a separate group of muscles was considered in accordance with the endogenous ability to overcome external resistance in a given direction. Dependence of contractile manifestations was coordinated in accordance with the approach or distance of areas of attachment of muscles. The positions of the muscles were regulated by the ventral and sagittal planes, as well as by the average amplitude of rotation. On the basis of the ratio of maximum, average amplitudes and frequency, data regarding the maximum overlaying of myofilaments in sarcomeres (maximum bioelectric activity), in accordance with the position angle of the movable segment of the lower extremity were obtained. It was established that for conducting functional testing, the location of the trunk and lower extremities in the same plane of movement and axis were the optimal positions for the diarticular muscles of the thigh and lower leg; for monoarticular extensors of the lower leg - a position at a right angle between the lower leg and thigh; for rotators of the lower leg and foot - location of these segments in a plane parallel to the sagittal one. On the basis of the obtained data, the optimal conditions for the mutual location of the segments of the kinematic links for the realization of the contractile capabilities of the muscles of the lower extremities have been determined, a protocol for functional testing of the muscles of the lower extremities has been developed, it is presented in graphic form with the possibility of entering data from both limbs, while test points of rotator muscles of the thigh and lower leg have been added.